Formation of a Tolerant Personality Through Theater Pedagogy - BUTUSOVA, Daria Olegovna; FAIZRAKHMANOVA, Lyalya Tagirovna; KAMALOVA, Ilmira Fuatovna; GLUZMAN, Alexander Vladimirovich (Utopía y Praxis Latinoamericana, 2020)
ABSTRACT The relevance of the problem of forming a tolerant personality is justified by the conditions of coexistence of representatives of different cultures within the same state, as well as at the level of their interstate interaction. The research allowed us to establish that the process of forming tolerance as a necessary quality of personality consists in the development of students´s interest in the problem of the multicultural world while relying on methods and technologies of theatre pedagogy allows them to form a holistic view of the world, establish a close connection with it and with themselves.RESUMEN La relevancia del problema de formar una personalidad tolerante se justifica por las condiciones de coexistencia de representantes de diferentes culturas dentro del mismo estado, así como a nivel de su interacción interestatal. La investigación nos permitió establecer que el proceso de formación de tolerancia como una cualidad necesaria de la personalidad consiste en desarrollar el interés de los estudiantes en el problema del mundo multicultural, mientras que depender de métodos y tecnologías de pedagogía teatral les permite formar una visión holística del mundo, establecer una conexión estrecha con él y con sí mismos.